Proposed marketing initiatives with new wave marketing approch for elevenia - Aditama Setiawan, Dani; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2018)
Abstract. Competition in e-commerce industry, especially in Indonesia, is getting tighter. Every e-commerce players are competing to attract the customers with various attractive campaign promotions. Today, Elevenia is in a very challenging position where the company must survive the competition among other e-commerce players who dare to "burn money" in order to offer lower to grab more customers. Since Salim Group took over Elevenia in 2017, Elevenia’s goal is more focus on long-term business growth & sustainability. In order to achieve its goals, Elevenia needs to minimize a high-cost marketing campaigns in order to generate positive net profits to build a strong business foundation in the long haul. Elevenia needs to find an effective way to develop a cost-efficient with high- impact marketing initiatives that can attract not only its website traffic, but also improving its purchase transaction number through its platform. Both internal and external factors that affect the business are analyzed to identify current business condition. The New Wave Marketing approach combines online and offline interaction between company and customer. This approach is used to generate an effective marketing initiatives which expected to help Elevenia to improve its business performance by increase its brand awareness and winning customer’s advocacy to grab more market share and accomplish its business goal. Keywords: Customer Advocacy, E-Commerce, Elevenia, Marketing Initiatives, New Wave Marketing